Mufti dan fatwa di negara-negara ASEAN - Wan Roslili Majid; Abdul Monir Yaacob (Institut Kefahaman Islam Malaysia, 1998)
Development of fatwas institutions, advisory opinions in Islamic law among ASEAN member countries; papers of a seminar.